The Criterion for Fulfilling Rights in Debts in Case of Increasing the Purchase Power of Money on Due Date of Obligation - ???? ??? ???, ??? ???? ???; ?????, ???? ???; ?????, ???? ??? (??? ? ????)
The value of credit money decreasing over time; but for some reason it may be increasing, as well. Given the decrease of the money value, there are clear jurisprudential views about amount of payment of the debt on due date; however, given the increase of the money value, what amount should the debtor pay? Answer to this important question is on one hand subject to accurate study of the dimensions of credit money and on the other hand to providing clear jurisprudential proofs. The hypothesis that this article is seeking to prove is that the purchase power of money in debt is the criterion for fulfillment of right in case of increase and decrease of money value. Therefore, in case of substantial increase of money value, payment of less nominal amount of money than the money received is unobjectionable; but in case of slight increase of money value, payment of the nominal amount is considered as full settlement of a debt.